2022
DOI: 10.1007/s10473-022-0609-7
|View full text |Cite
|
Sign up to set email alerts
|

Global well-posedness of a Prandtl model from MHD in Gevrey function spaces

Abstract: We consider a Prandtl model derived from MHD in the Prandtl-Hartmann regime that has a damping term due to the effect of the Hartmann boundary layer. A global-in-time well-posedness is obtained in the Gevrey function space with the optimal index 2. The proof is based on a cancellation mechanism through some auxiliary functions from the study of the Prandtl equation and an observation about the structure of the loss of one order tangential derivatives through twice operations of the Prandtl operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The key observation in [8,17] is about some kind of intrinsic structure that is similar to hyperbolic feature for one order loss of tangential derivatives. Recently, inspired by the stabilizing effect of the intrinsic hyperbolic type structure, Li-Xu-Yang [22] showed the global well-posedness of a Prandtl Model from MHD in the Gevrey 2 setting. The hyperbolic Prandtl system (1.1) is more complicated in terms of loss of derivatives due to the quasi-linear term η∂ t (u • ∂ x u + v∂ y u).…”
Section: Introductionmentioning
confidence: 99%
“…The key observation in [8,17] is about some kind of intrinsic structure that is similar to hyperbolic feature for one order loss of tangential derivatives. Recently, inspired by the stabilizing effect of the intrinsic hyperbolic type structure, Li-Xu-Yang [22] showed the global well-posedness of a Prandtl Model from MHD in the Gevrey 2 setting. The hyperbolic Prandtl system (1.1) is more complicated in terms of loss of derivatives due to the quasi-linear term η∂ t (u • ∂ x u + v∂ y u).…”
Section: Introductionmentioning
confidence: 99%
“…The key observation in [8,17] is about some kind of intrinsic structure that is similar to hyperbolic feature for one order loss of tangential derivatives. Recently, inspired by the stabilizing effect of the intrinsic hyperbolic type structure, Li et al [22] showed the global well-posedness of a Prandtl Model from MHD in the Gevrey 2 setting.…”
Section: Introductionmentioning
confidence: 99%